Tip Withering Bug, Anoplocnemis phasiana (Fab.), Halts Grape Shoots: Friend or Foe, Arrival Time Explains - P D Kamala Jayanthi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
Pruning is a regular practice followed in grapevine, Vitis vinefera L., to keep the vine manageable and productive. However, immediately after pruning, the plants put out a new flush of leaves which attract several leaf-feeding insects, leading to defoliation and crinkling. Incidence of tip withering bug, Anoplocnemis phasiana (Fab.), usually coinciding with the period of halting practice, results in die-back of shoot tip and prevents extension of the shoot, thus halting shoot growth. Intricacies involved in incidence of this coreid bug on grapevine are discussed here.